Teaching strategies for gifted students in mathematics and literacy : a case study in a New Zealand primary school : a thesis presented in partial fulfillment of the requirements for the degree of Master of Education at Massey University - Lilley, Katherine (Massey University, 2008)
To date there is little New Zealand based research of gifted students in their regular classrooms and to address this issue, this qualitative case study has been undertaken. Three research aims firstly examine the strategies regular classroom teachers use to provide teaching and learning experiences in mathematics and literacy to cater for the identified needs of gifted students; investigate the views of the teachers and gifted students about teaching and learning programmes in mathematics literacy, and lastly provide descriptive examples of how teachers in Years 4-6 primary school classrooms are catering for their gifted students' diverse learning needs. Data has been gathered through observations of teachers and gifted students in their classroom environments using a Classroom Observation Focus, by conducting semi-structured interviews of both teachers and gifted students, and through document collection. An analysis of the data identified themes that have contributed to the findings of this research. The teachers in this research represent a range of teaching experiences with each teacher having different opportunities to work with gifted students. All of the teachers saw their role in the classroom as one of assessing and teaching to their students' learning needs. These research findings provide important discussion points about the similarities between the strategies used by the three teachers in mathematics and literacy teaching. The findings also suggest successful teaching strategies to promote gifted students' learning, in mathematics and literacy, are reliant on the teacher's understanding of giftedness and their understanding of the processes of differentiation as a way to provide for gifted learners in the regular classroom environment. Research findings also indicate that the perspectives of the gifted students, determined by eliciting their views on what was happening in their classrooms, are pivotal in ensuring a gifted student's learning needs are catered for. It is important then for teachers to consider how they are providing challenge, choice, and flexibility for these unique and diverse students within the regular classroom environment.
Keywords: Gifted children, New Zealand; Primary school education, New Zealand; Mathematics study; Literacy